Windows Server 2012 unleashed - Morimoto, Rand; Noel, Michael; Droubi, Omar; Abbate, Andrew; Yardeni, Guy; Amaris, Chris (Sams, 2012)
A comprehensive and realistic guide to Windows Server 2012 planning, design, prototyping, implementation, migration, administration, and support. Every chapter contains tips, tricks, best practices, and lessons learned from actual deployments.